Reading fear in Flavian epic emotion, power and stoicism, - Agri, Dalida ca. 20./21. Jh (Oxford Academic, 2022)
Notes on Texts and Abbreviations -- Introduction -- 0.1 Outline, Context, and Approach -- 0.2 Ancient Interactions Between Poetry and Philosophy -- 0.3 Scholarship on Emotions and Stoic Influences in Flavian Epic -- 0.4 Stoic Views on Emotion -- 0.5 What Is an Emotion? The Greek Stoic Legacy in Roman Thought -- 0.6 Seneca on Poetry -- 0.7 Stoics Views on Kingship and Tyranny -- 0.8 The So-called 'Stoic Opposition' -- 0.9 The Tyrant in the Poetic Tradition -- 0.10 Structure of the Argument -- 1. Fear in Flavian Representations of Epic Tyrants: Depictions and Uses of Emotion -- 1.1 Valerius Flaccus' Argonautica: King Pelias -- 1.1.1 Statius' Thebaid: Polynices -- 1.1.2 Statius' Thebaid: King Creon -- 1.2 Silius Italicus' Punica: Hannibal -- 2. Reading Fear in Valerius Flaccus' Argonautica -- 2.1 Fear and Hope -- 2.2 Fear and Prophecy -- 2.3 Fear, Divine Will, and Human Agency -- 2.4 Medea: Between Power and Vulnerability -- 2.4.1 The Proserpina Simile -- 2.4.2 Fear and the Female Body -- 2.4.3 Stoic Resistance? -- 2.4.4 Reverse Sex Similes -- 3. Reading Fear in Statius' Thebaid -- 3.1 Tisiphone or the Incarnation of the Passions -- 3.2 Fear as a Political Idea -- 3.3 Fear, Power, and Agency -- 4. Reading Fear in Silius Italicus' Punica -- 4.1 Rome on Carthage: The 'War on Terror' -- 4.2 Fear, cupido gloriae, and the Horse Analogy -- 4.3 Carthage, Tyranny, and 'the Fear Within' -- Epilogue -- Bibliography -- Index Locorum -- General Index